Influence of vibration on delayed onset of muscle soreness following eccentric exercise - Bakhtiary, A. H.; Safavi-Farokhi, Z.; Aminian-Far, A. (British Journal of Sports Medicine, 2007)
Delayed onset muscle soreness (DOMS), which may occur after eccentric exercise, may cause some reduction in ability in sport activities. For this reason, several studies have been designed on preventing and controlling DOMS. As vibration training (VT) may improve muscle performance, we designed this study to investigate the effect of VT on controlling and preventing DOMS after eccentric exercise.